Peran Orang Tua dalam Pembelajaran Daring di Sekolah Dasar - Pujiastuti Pujiastuti; Ayuhan Ayuhan (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2022)
This research was motivated by curiosity what is the role of parents when accompanying children to do chores at home during the pandemic. This study aims to determine (1) the role of parents in online learning at SDN Kembangan Utara 09 Pagi Jakarta Barat, (2) Efforts by parents in increasing the seriousness of students in online learning at SDN Kembangan Utara 09 Pagi Jakarta Barat and (3) the obstacles faced faced by parents in online learning at SDN Kembangan Utara 09 Pagi, Jakarta Barat. The methodology of this research is qualitative. The subjects in this study were parents and homeroom teachers for grade II at SDN Kembangan Utara 09 Pagi, Jakarta Barat. Data collection was taken through interviews, observation, documentation. The author acts as a direct interviewer to collect data through parents and second grade homeroom teachers. The results showed that (1) The role of parents in online learning at SDN Kembangan Utara 09 Pagi Jakarta Barat is to have three roles at once, namely the role of parents, breadwinners and teachers at home (2) The efforts of parents in increasing the seriousness of students in online learning at SDN Kembangan Utara 09 Pagi Jakarta Barat is to provide motivation, guidance and assistance (3) Obstacles faced by parents in online learning at SDN Kembangan Utara 09 Pagi Jakarta Barat are limited infrastructure facilities, such as mobile phones, motivation, internet quota and time. Keywords : Parents, Online Learning and Motivation